Camellia renshanxiangiae, a synonym of C. punctata (Theaceae) - Zhang, Ya-Li; Yu, Xiang-Qin; Jiang, Yin-Zi; Wu, Yin; Yang, Shi-Xiong (Phytotaxa, 2023)
Camellia renshanxiangiae is the first reported camellias with hairy anthers, which is a feature that has been ignored by previous scholars, and which also occurs in C. punctata. Since no substantial differences between C. renshanxiangiae and C. punctata were found, the former was reduced into the latter as a heterotypic synonym. In addition, the name Thea punctata is lectotypified here.